A Multimodal Analysis of Loreal Paris X Cinta Laura Khiel Advertisement - Rianti, Aurellya Mitha Eka Ayu; Nurlaila, Nurlaila (International Journal of English and Applied Linguistics (IJEAL), 2024)
One of the texts with nuanced meanings is an advertisement. When discussing how to effectively convey messages in advertisements, the complexity of meaning encompasses both written and visual components. To understand the power and meaning of a text that contains multiple modes, such as verbal, visual, and aural, a multimodal analysis of an advertisement is necessary to understand the complexities of meaning. The research aims to examine the multimodal resources in the Loreal x Cinta Laura Khiel advertisement on YouTube based on five semiotic multimodal systems proposed by Anstey &Bull (2018). This research utilizes both qualitative and descriptive techniques. The information was obtained as a picture derived from a screenshot of a YouTube commercial. The outcome depicts five components of the multimodal system in this advertisement: verbal, visual, auditory, gestural, and spatial. These five factors are mutually beneficial for communicating messages from the Loreal advertisement on Loreal Official YouTube and advertising and marketing this smart application.